The role of institutional ownership on the relationship between CEO overconfidence and the risks of companies listed on the Tehran Stock Exchange - Beranoosh Karimi (New Applied Studies in Management, Economics & Accounting, 2023)
The aim of this study, investigating the role of institutional ownership on the effect of the CEO's overconfidence on the risks of companies listed on the Tehran Stock Exchange. The statistical sample includes 82 companies during the period of 2012 to 2021. Hypotheses testing was performed using linear regression and using Eviews software. The research results showed that the CEO's overconfidence has a significant and direct effect on the company's future risk, but the CEO's overconfidence does not have a significant effect on the company's operational risk. Also, other research results show that institutional ownership reduces the effect of CEO's overconfidence on the company's future risk, while institutional models do not moderate the effect of CEO's overconfidence on the company's operational risk